Smoking and red blood cell phospholipid membrane fatty acids. (September 2016) - Murff, H.J.; Tindle, H.A.; Shrubsole, M.J.; Cai, Q.; Smalley, W.; Milne, G.L.; Swift, L.L.; Ness, R.M.; Zheng, W.
Abstract: Smoking is associated with lower n-3 long chain polyunsaturated fatty acids (LCPUFA) concentrations; however, limited studies have accounted for dietary PUFA intake or whether tobacco dose or smoking duration influences this association. We measured red blood cell phospholipid (RBC) membrane concentrations of fatty acids in 126 current smokers, 311 former smokers, and 461 never smokers using gas liquid chromatography and tandem mass spectrometry. Smokers had lower RBC membrane percentages of total n-3 LCPUFAs compared to former smokers or never smokers (median percent: 5.46, [interquartile range (IQR) 4.52, 6.28] versus 6.39; [IQR: 5.18, 7.85] versus 6.59; [IQR 5.34, 8.01]) (p<0.001) and this association remained after adjusting for dietary PUFA intake. Duration of smoking and cigarettes per day were not associated with RBC membrane n-3 LCPUFA differences. Smoking is associated with lower n-3 LCPUFA RBC membrane percentages and this association was not influenced by diet or smoking dose or duration. Highlights: Smokers have lower RBC membrane n-3 long-chain PUFA levels compared nonsmokers. Dietary intake of n-3 long-chain PUFAs does not explain these differences. Cigarettes smoked per day does not impact RBC n-3 long-chain PUFA levels.